Ectopic ureter draining a poorly functioning renal moiety can be missed by IVP but not by MRU - (:unkn) unknown (My University, 2007)
Ectopic ureter draining a poorly functioning renal moiety can be missed by classical radiological methods such as ultrasonography, voiding cystourethrogram and intravenous pyelogram. In such conditions, use of computerized tomography and magnetic resonance imaging have been advocated to diagnose poorly functioning, abnormal duplex collecting system and ectopic ureter. A case of a 16-year old girl with continuous dribbling incontinence and normal IVP and cystoscopy findings whose ectopic ureter and duplicated system could only be diagnosed by MRU is presented in this case report.
Keywords: Ectopic ureter; IVP; MRU; Urinary incontinence/physiopathology